The Impact of Different Degrees of Intraventricular Hemorrhage on Mortality and Neurological Outcomes in Very Preterm Infants: A Prospective Cohort Study - Wang, Yong; Song, Juan; Zhang, Xiaoli; Kang, Wenqing; Li, Wenhua; Yue, Yuyang; Zhang, Shan; Xu, Falin; Wang, Xiaoyang; Zhu, Changlian (Frontiers in Neurology, 2022)
Objective: Intraventricular hemorrhage (IVH) is a common complication in preterm infants and is related to neurodevelopmental outcomes. Infants with severe IVH are at higher risk of adverse neurological outcomes and death, but the effect of low-grade IVH remains controversial. The purpose of this study was to evaluate the impact of different degrees of IVH on mortality and neurodevelopmental outcomes in very preterm infants. Methods: Preterm infants with a gestational age of <30 weeks admitted to neonatal intensive care units were included. Cerebral ultrasound was examined repeatedly until discharge or death. All infants were followed up to 18–24 months of corrected age. The impact of different grades of IVH on death and neurodevelopmental disability was assessed by multiple logistic regression. Results: A total of 1079 preterm infants were included, and 380 (35.2%) infants had grade I-II IVH, 74 (6.9%) infants had grade III-IV IVH, and 625 (57.9%) infants did not have IVH. The mortality in the non-IVH, I-II IVH, and II-III IVH groups was 20.1%, 19.7%, and 55.2%, respectively (p < 0.05), and the incidence of neurodevelopmental disabilities was 13.9%, 16.1%, and 43.3%, respectively (p < 0.05), at 18–24 months of corrected age. After adjusting for confounding factors, preterm infants with III-IV IVH had higher rates of cerebral palsy (26.7% vs. 2.4%, OR = 6.10, 95% CI [1.840–20.231], p = 0.003), disability (43.3% vs. 13.9%, OR = 2.49, 95% CI [1.059–5.873], p = 0.037), death (55.2% vs. 20.1%, OR = 3.84, 95% CI [2.090–7.067], p < 0.001), and disability + death (73.7% vs. 28.7%, OR = 4.77, 95% CI [2.518–9.021], p < 0.001) compared to those without IVH. However, the mortality and the incidence of neurodevelopmental disability in infants with I-II IVH were similar to those without IVH (p > 0.05). Conclusions: Severe IVH but not mild IVH increased the risk of mortality and neurodevelopmental disability in very preterm infants.